Sistematização da aplicação da linha de balanço em obras roviárias planejadas que utilizaram diferentes técnicas de programação de execução - Mota, Ítalo Ponte Der Hovannessian (2017)
In the highway constructions, as well as in other works, the appropriate planning is the priority basis for a low-cost execution, lower environmental impact and reduction at run time. Road works are either state or federal highway concessions, are bidded and the low cost established by the organs for execution, oblige the contractor to elaborate a thorough strategic planning for each piece of work. Planning aims to reduce the deadlines and direct and indirect costs of the work, using all available resources to perform services on several fronts, reducing the runtime and idleness of the equipment. In this high-competitiveness scenario, companies that better plan themselves will therefore have better conditions to reduce prices, thereby obtaining a greater advantage in public competition. Thus, the present work aims to systematize the application of the technique balance line to long-term planning of road works. The systematic programming has been applied to two case studies using planning data elaborated for participation in competition, these provided by two large companies that operate heavily in the country's infrastructure sector. When comparing the total lifetime of the original planning with its reprogramming using the systematic, it was obtained for the company case study to a reduction of 12.83% of days of execution, equivalent to 69 days and for the case study of the company B an increase of 0.26% of days of execution, which equals two days. By applying this systematic the scheduling of road works, planners have the opportunity to identify small discrepancies in planning, where other techniques do not allow, thus elaborating more efficient schedules.